Nutraceutical with a promising oral anticancer effect: in vitro study on apricot oil extract - Ellithy, Marwa Mohamed (2023)
One of the major threats to human health is malignancy. Treatment regimens usually followed by either chemo or radiotherapy have a wide range of collateral unwanted side effects. Scientists seek alternatives with less or no adverse consequences. Nutraceuticals possess disease-modifying implications in medicine related to Alzheimer’s, cardiovascular, Parkinson’s diseases and malignancy. Apricot oil extract is one such nutraceutical. Its active component is amygdalin, known also as vitamin B.17 or laetrile. It is found in a wide range of vegetable species. Amygdalin is found in high concentration in the kernels of rosaceous fruits such as bitter nuts and apricot kernels. Amygdalin is an aromatic cyanogenic component with a glycoside group. It has a diverse effect on different systems and organs of the body. Recently, it has shown an anticancer potential as it can decompose carcinogenic elements found in the body and kill malignant cells, so it results in cancer growth inhibition. There is a great debate related to the cyanide toxicity of amygdalin.